3D magnetization currents, magnetization loop, and saturation field in superconducting rectangular prisms. (16th May 2017) - Pardo, E; Kapolka, M
Abstract: Bulk superconductors are used in many applications and material characterization experiments, with the bulk shape of the rectangular prism being the most frequent. However, the magnetization currents are still mostly unknown for this kind of 3D shape, especially below the saturation magnetic field. Knowledge of the magnetization currents in this kind of sample is needed to interpret the measurements and the development of bulk materials for applications. This article presents a systematic analysis of the magnetization currents in square-based prisms of several thicknesses. We make this study by numerical modeling using a variational principle that enables a high number of degrees of freedom. We also compute the magnetization loops and saturation magnetic field, using a definition that is more relevant for thin prisms than previous ones. The article presents a practical analytical fit for any aspect ratio. For applied fields below the saturation field, the current paths are not rectangular, presenting 3D bending. The thickness-average results are consistent with previous modeling and measurements for thin films. The 3D bending of the current lines indicates that there could be flux-cutting effects in rectangular prisms. The component of the critical current density in the applied field direction may play a role, with the magnetization currents being different in a bulk and a stack of tapes.